Covariation of brain and skull shapes as a model to understand the role of crosstalk in development and evolution. Issue 1 (14th November 2022) - Conith, Andrew J.; Hope, Sylvie A.; Albertson, R. Craig
Abstract: Covariation among discrete phenotypes can arise due to selection for shared functions, and/or shared genetic and developmental underpinnings. The consequences of such phenotypic integration are far‐reaching and can act to either facilitate or limit morphological variation. The vertebrate brain is known to act as an "organizer" of craniofacial development, secreting morphogens that can affect the shape of the growing neurocranium, consistent with roles for pleiotropy in brain–neurocranium covariation. Here, we test this hypothesis in cichlid fishes by first examining the degree of shape integration between the brain and the neurocranium using three‐dimensional geometric morphometrics in an F5 hybrid population, and then genetically mapping trait covariation using quantitative trait loci (QTL) analysis. We observe shape associations between the brain and the neurocranium, a pattern that holds even when we assess associations between the brain and constituent parts of the neurocranium: the rostrum and braincase. We also recover robust genetic signals for both hard‐ and soft‐tissue traits and identify a genomic region where QTL for the brain and braincase overlap, implicating a role for pleiotropy in patterning trait covariation. Fine mapping of the overlapping genomic region identifies a candidate gene, notch1a, which is known to be involved in patterning skeletal and neural tissues during development. Taken together, these data offer a genetic hypothesis for brain–neurocranium covariation, as well as a potential mechanism by which behavioral shifts may simultaneously drive rapid change in neuroanatomy and craniofacial morphology. Abstract : We measure and detect covariation between the brain and the neurocranium in an F5 hybrid population of cichlid fish. By mapping these traits, we uncover a pleiotropic locus that may underlie covariation and provide a means to modulate behavior and head shape simultaneously. Research highlights: Covariation among traits can arise due to shared functional, developmental, and/or genetic underpinnings. We measure and detect covariation between the brain and the neurocranium in an F5 hybrid population of cichlid fish. By mapping these traits, we uncover a pleiotropic locus that may underlie covariation and provide a means to modulate behavior and head shape simultaneously.